Comparative analysis of hyaluronan gel and xanthan-based chlorhexidine gel, as adjunct to scaling and root planing with scaling and root planing alone in the treatment of chronic periodontitis: A preliminary study - Avinash Singh Chauhan; Vivek K Bains; Vivek Gupta; G P Singh; Sudhir S Patil (Wolters Kluwer Medknow Publications, 2013)
Aim : The aim of this study was to evaluate the effects of hyaluronan (HA) and chlorhexidine (CHX) gels as adjunct to scaling and root planing (SRP) in the treatment of chronic periodontitis. Materials and Methods: Sixty patients within the age group of 30-65 years recruited to participate in the study were randomly equally divided into three groups. Complete SRP and subgingival debridement were performed within 6 h in all the patients. For control (Group I) patients, SRP was the only treatment modality given; for Group II and III patients, at least 8 teeth with 4-8 mm probing pocket depth (PPD) were selected for subgingival application of HA gel and CHX gel, respectively. Clinical periodontal parameters such as gingival index, PPD, and clinical attachment level (CAL) were recorded at baseline and 3 months, whereas plaque index was recorded at baseline, 1 month, and 3 months. For measuring systemic/hematological parameters, blood samples for laboratory tests for total leucocyte count (TLC), differential leucocyte count (DLC), and C-reactive protein (CRP) were obtained using standard 2-mL syringe from each subject in all the three groups at baseline, 24 h, and on the 1 month and 3 months post-baseline. Results: In all the three groups, a significant reduction in PPD and gain in CAL were observed between baseline and 3 months follow-up ( P < 0.05); however, at 3 months, change in PPD and CAL was more in Group II than Group III, but the difference was non-significant, and Group I (control) showed less changes in PPD and CAL than both experimental groups. Only one patient revealed positive value for CRP at baseline only, and hence could not be statistically analyzed. In all the three groups, the peak values for TLC count were observed at 24 h. At 1-month and 3-month intervals, a significant improvement in TLC and DLC counts was observed among the experimental (HA gel/SRP and Xan-CHX gel) groups as compared to control group (SRP alone).